Response of Rangeland Vegetation to Recent Trends in Seasonal Climate in Mansehra, Pakistan: Rangeland response to the recent climate trends - Fatima, Naheed; Kausar, Rukhsana; Ashraf, Arshad; Iqbal, Muhammad Bilal; Nawaz, Qurat-ul-Nain (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
The deterioration of rangeland resources as a result of environmental changes is a serious concern in the Himalayan mountainous region of Pakistan. The present study is aimed to evaluate the response of vegetation cover of rangeland to recent trends in climate parameters, such as the seasonal temperature and rainfall in the Mansehra district of Khyber Pakhtunkhwa province, Pakistan. Correlation analysis was performed between the MODIS data products, i.e., NDVI (Normalized difference vegetation index) and LST (Land surface temperature), and TRMM rainfall datasets of the 2000-2018 period. NDVI indicated a negative correlation with LST of winter (R= -0.56), spring (R= -0.7), summer (R= -0.24), and autumn (R= -0.23) significant (p<0.05) for winter and spring seasons only. In contrast, the correlation of NDVI was observed positive with seasonal rainfall exhibiting coefficient of correlation values of 0.41, 0.79, 0.64, 0.7 for winter, spring, summer, and autumn significant (p<0.05) for the last two seasons only. The low correlation observed between NDVI and LST of summer and autumn seasons is likely because of the prevailing stress condition of chlorophyll contents of the vegetation cover under warming conditions. However, this situation appears to be compensated by the rainfall as indicative of the moderate to strong correlation between the NDVI and rainfall of these two seasons. The least NDVI values observed during the winter season indicate limited vegetation cover for grazing opportunities in the lower valleys. However, an in-depth investigation of production patterns would further facilitate analyzing the grazing potential to support decision-making for long-term grazing management.